(untitled) (Research, Society and Development, 2020)
Parkinson’s disease affects the central nervous system, causing dysfunctional dopamine production. This directly affects the motor system, leading to the loss of voluntary movements, joint stiffness, limb tremors, and imbalance. Palliative treatments are applied to alleviate symptoms of the disease and improve quality of life. Considering functional changes and symptoms that are generated by Parkinson’s disease, pain is also a debilitating factor that can severely affect the individual. The present study investigated the mean age, duration of involvement, body locus incidence, and interference with quality of life by pain in patients with Parkinson’s disease. We applied a one-dimensional, subjective, and qualitative Visual Analog Scale and the multidimensional and interpretative Wisconsin Brief Pain Inventory. The study was conducted with 36 participants of both genders (mean age: 65.5 years for men and 72.0 years for women). The incidence of pain was detected in 87.5% of the participants. We found that pain occurred more frequently in the upper limbs and interfered with the performance of general activities. Treatment by a multidisciplinary team in all dimensions of the disease is needed to alleviate patients’ pain and consequently improve their quality of life.